2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24512
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Institutional Evaluation of Engineering Discipline Selection

Abstract: During the fall of 2014, a quantitative study of first-year engineering student discipline selection was conducted at four dissimilar institutions in the Midwest: (1) an Urban Public, (2) a Private, (3) a Large Land Grant, and (4) a Large Urban. At all four institutions, an on-line survey was conducted at the start and at the end of the semester. The questions related to how interested students are in engineering (as compared to other academic majors), how certain they are that engineering is the best field of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…This data was initially analyzed across three institutions and presented in a past ASEE paper that found that the firstyear engineering experience tends to be a polarizing experience either increasing or decreasing students interest (and likely commitment) to engineering. 13 Further, that study found that the type of institution was an important factor to student major selection, and the authors postulate that those programs may attract a certain "type" of engineering student with different expectations or commitment levels. 13 The survey used in this work also included questions related to a student's choice of major.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This data was initially analyzed across three institutions and presented in a past ASEE paper that found that the firstyear engineering experience tends to be a polarizing experience either increasing or decreasing students interest (and likely commitment) to engineering. 13 Further, that study found that the type of institution was an important factor to student major selection, and the authors postulate that those programs may attract a certain "type" of engineering student with different expectations or commitment levels. 13 The survey used in this work also included questions related to a student's choice of major.…”
Section: Methodsmentioning
confidence: 99%
“…13 Further, that study found that the type of institution was an important factor to student major selection, and the authors postulate that those programs may attract a certain "type" of engineering student with different expectations or commitment levels. 13 The survey used in this work also included questions related to a student's choice of major. These questions are the focus for this work.…”
Section: Methodsmentioning
confidence: 99%
“…8 Common techniques for investigating the motivations behind entering engineering include text analysis of essays on why students chose engineering and Likert scale survey questions including a statistical comparison, Wilcoxon rank-sum test, of results for different groups. 9 This research used both techniques: text analysis of essays guided the development of a Likert scale survey which was quantitatively analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First-year engineering students are more certain of choosing engineering as a whole compared to choosing what discipline within engineering. 9 First-year engineering courses also help students determine their interests in the different engineering disciplines. 15 Other sources of information that students commonly use to decide on a discipline include personal exploration, peer discussion, and advice from professors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First-year engineering courses have been added to the engineering curriculum over the past 30 to 40 years in an effort to engage the students in engineering at an earlier time 1 , improve retention 2 , provide an introduction to engineering disciplines 3 , inspire the student for the study of engineering, have students recognize the importance of engineering in our modern way of life, etc. Even though there is general agreement on the objectives of the course, the course content used for these courses varies widely 4 .…”
Section: Introductionmentioning
confidence: 99%